A influência da governança democrática no desenvolvimento socioambiental das cidades brasileiras - Freitas, Verivaldo Alves de (2022)
Public governance is seen from several perspectives that lead to a new way of thinking about the capacities of the State and about the relations between it and society. In this study, public governance is highlighted in an approach to democratic governance. The general objective of this research is to investigate the influence of democratic governance mechanisms on the socio-environmental development of Brazilian cities. The study has a quantitative and descriptive nature, making use of statistical models. To test them, we used a sample of 677 municipalities in Brazil, distributed in five geographic regions. The data were collected in the year 2021. The databases of the consultancy Urban Systems, the Federal Council of Administration (CFA), and the Brazilian Institute of Geography and Statistics (IBGE) were used as secondary data sources. The statistical models shown by this stricto sensu academic demand were empirically tested, applying the multiple linear regression model by the Ordinary Least Squares (OLS) method, using the Stata® software. To carry out the tests, two constructs were used, expressed in the sequence. 1) Democratic Governance, taking as a measure the indicators of public transparency, municipal public policy councils and citizen service via app or website, which are part of the “Governance” axis of the Connected Smart Cities (CSC). 2) Socio-environmental Development, using as measures the indicators of education, health, safety and sanitation, as well as the environment of the IGM/CFA. The results infer a positive and significant influence, only, of public transparency in the development in education and health, and of the service to the citizen by app or website in the development in public security. Finally, the studies that converge with the results of this experiment postulate the argument that democratic governance, through citizen participation, is capable of contributing to the development of democracy and Brazilian cities. These discussions are driving a theoretical debate on citizen participation in public management and political decisions, suggesting a more advanced assessment of this relationship, based on its interconnection and particularities, as Brazil has challenging characteristics, due to its size and social inequalities.